Studi Islam dan Tantangan Hoaks Keagamaan: Analisis Konseptual dan Strategi Penanggulangan di Era Digitalisasi - Ikhsan, Muhammad; Ferdianur, Ferdianur; Mukmin, Mukmin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the dissemination patterns of religious hoaxes in the digital era, identify factors that increase public vulnerability, and explain how Islamic Studies provides a conceptual framework for verifying and countering religious misinformation. The research employs a literature review method, drawing on recent scholarly publications selected through inclusion criteria and examined using thematic content analysis. The findings indicate that religious hoaxes spread predominantly through private communication channels and algorithm-driven platforms that amplify emotionally charged content. Low digital and religious literacy, psychological biases, and emerging digital authorities significantly heighten susceptibility to misinformation. Islamic Studies offers essential verification tools such as tabayyun, hadith criticism, hermeneutics, and maqashid al-sharia to assess the authenticity of religious information. The study concludes that effective mitigation requires an integrative strategy combining digital religious literacy, institutional collaboration, and technological verification systems.   Keywords: religious hoaxes, Islamic Studies, digitalization